Implementation of Corrective Maintenance on CNC Glass Milling Machine in Glass Manufacturing Company - Yuyun Yuniar Rohmatin; Wahyuni, Rossi S.; Mei Raharja; Muhammad Irvan R (Jurnal Ilmiah Teknik, 2025)
CNC Glass milling machines used to cut, shape, or smooth glass surfaces to make glasses, bowls and other household items. This study uses a mix-method approach to identify machine components and determine maintenance standards for CNC Glass Milling Machines. The results a show that the CNC Glass Milling Machine is specifically designed to process glass with high precision. CNC Glass Milling machine is scheduled routinely as many as 6 times every Friday every week. The standard maintenance of the work table on the machine is a looking at the cleanliness no dirt or dust flakes if there is dirt cleaned using a brush as a cleaning tool, the standard maintenance of monitor is done visually by looking at the condition of the monitor screen can display parameter settings, error messages, object coordinate positions or not